Recent Advances in the development of User-friendly Software Tools for Computational Protein Design, Modeling, and Molecular Docking - Joshua, Magezi; Syrus, Semawule; Magdalene, Namuswe; Nwankwo, Janice Adaeze (International Journal of Environment, Agriculture and Biotechnology, 2024)
Computational protein design, modeling, and Molecular Docking represent a group of vital in-silico methods employed in predicting protein sequences with desired functions, predicting protein structures, and several molecular interactions with proteins. The application of such in silico methods is seen in the screening of potential targets during new drug designs, the discovery of novel protein sequences that could play new and vital functions such as industrial processes, understanding of protein function by studying its residues, and understanding of the effects of position mutations to the structure and function of the protein. This means these tools find a lot more use in protein-related research. However, many scientists are basic computer users and not experts in utilizing sophisticated software involved in in-silico Protein methods. This limits the progress of mainly young researchers towards protein-related research ideas. This review therefore discusses the progress in the development of user-friendly tools for assisted Insilco protein design, modeling, and docking.